2020
DOI: 10.3390/ijms21020554
|View full text |Cite
|
Sign up to set email alerts
|

Riboflavin Plays a Pivotal Role in the UVA-Induced Cytotoxicity of Fibroblasts as a Key Molecule in the Production of H2O2 by UVA Radiation in Collaboration with Amino Acids and Vitamins

Abstract: To investigate environmental factors that contribute to ultraviolet A (UVA)-induced oxidative stress, which accelerates the senescence and toxicity of skin cells, we irradiated human fibroblasts cultured in commonly used essential media with UVA and evaluated their viability and production of reactive oxygen species. The viability of fibroblasts exposed to a single dose of 3.6 J/cm2 UVA was not reduced when cultured in Hanks balanced salt solution, but it was significantly decreased when cultured in Dulbecco’s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 44 publications
1
7
0
1
Order By: Relevance
“…These results are in agreement with those reported in the literature showing the deleterious effects of H2O2 on dermal fibroblasts [59,60].…”
supporting
confidence: 93%
“…These results are in agreement with those reported in the literature showing the deleterious effects of H2O2 on dermal fibroblasts [59,60].…”
supporting
confidence: 93%
“…This reaction suggests the increased rate of vitamin C degradation (loss) in food products like milk in the presence of sunlight ( Ottaway, 1993 ; de La Rochette et al, 2000 ). This implies that photo-oxidation of vitamin C is significantly reduced in the absence of riboflavin ( Yoshimoto et al, 2020 ). Riboflavin-folic acid: …”
Section: Discussion Of Literature Synthesismentioning
confidence: 99%
“…On the other hand, some research groups have shown that the coexistence of multiple components induces stronger cytotoxicity than a single photosensitizer condition [44,51]. It has been reported that a low concentration of photocatalyst, about 0.4 μg/mL riboflavin, can induce cell damage in coexisting conditions with amino acids and vitamins [52]. On the other hand, in single riboflavin conditions, it takes about 100 μg/mL of riboflavin to induce cell toxicity in vitro [53].…”
Section: Study Of Uva-photosensitization In Vitromentioning
confidence: 99%
“…Those results indicate that the oxidative degradation of folic acid proceeds only very slowly in HBSS containing folic acid alone, but occurs rapidly in the presence of the photosensitizer riboflavin. Since this reaction was not inhibited by NaN 3 , a singlet oxygen scavenger, it was thought that the oxidative degradation of folic acid was possibly promoted via photosensitization of type I generated by riboflavin photosensitization [52]. Therefore, it is considered that the superoxide quencher is effective for these types of reactions.…”
Section: Combination Of Components With Type I As the Main Reaction (...mentioning
confidence: 99%